If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 83x + -166 = 83x + 166 Reorder the terms: -166 + 83x = 83x + 166 Reorder the terms: -166 + 83x = 166 + 83x Add '-83x' to each side of the equation. -166 + 83x + -83x = 166 + 83x + -83x Combine like terms: 83x + -83x = 0 -166 + 0 = 166 + 83x + -83x -166 = 166 + 83x + -83x Combine like terms: 83x + -83x = 0 -166 = 166 + 0 -166 = 166 Solving -166 = 166 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 83x+83=83x+-83 | | 2(8x-2)=-84 | | 7p+11=2p-4 | | Y=2(X-9) | | 3/4y-1/2=5/8y+1 | | 2(5x-1)=-82 | | -8(-4x-5)=-88 | | 2x+3=6+2x | | -7(8x+3)=-133 | | 4m+7=34 | | 240+.25m=412.50 | | p=100+-4Q | | 2x-14+5=-6+11 | | 15=10y-4y-3 | | 2(-7b+1)=-35 | | 9(3x-1)=4x-6x | | 2(7x-2)+3=-99 | | 2(4-2x)=-x+1 | | c^2+8cy+15y^2= | | x^4+2x^2+47=0 | | 3y+y=164 | | X^2-X=4X | | x^4+x^2+47=0 | | 4b^2+14b+60=0 | | 6+5x-8x=15 | | 8(z-9)=-22 | | y=-40+6x | | 13=-13b+5b | | v^2+14v+60=0 | | 7x-5=47.5 | | -3z+7z=-3z-3-z | | 3×4/5 |